Analysis of Narrow Band PLC Technology Performance in Low-Voltage Network - Pyda, D.; Habrych, M.; Rutecki, K.; Miedzinski, B. (Elektronika ir Elektrotechnika, 2014)
Although the PLC technology is increasingly used mainly in low voltage networks, causes of interference of signal transmission have not been, as yet, sufficiently explained. It is very important for the wider use of this technology in practice. The paper presents and discusses the results of simulation analysis of transmission efficiency for narrow band PRIME standard obtained for specially developed for this purpose simulation model of the real low voltage network. This model allows both the mapping of the network parameters in the desired range as well as the modelling of physical phenomena occurring in it that may practically affect the narrow-band transmission quality. On the basis of the results the suitable conclusions for practical applications have been formulated. DOI: http://dx.doi.org/10.5755/j01.eee.20.5.7101